SEKOLAH MENYENANGKAN: KONSEP SEKOLAH YANG MEMPROMOSIKAN WELL-BEING BERDASARKAN SUARA ANAK-ANAK, ORANGTUA DAN GURU DI INDONESIA: GROUNDED ANALISIS - T. Novi Poespita Candra; Muhammad Nur Rizal (Jurnal Psikologi Integratif, 2021)
Many studies emphasized the importance on how schools expand their role beyond the academics improvement, particularly in terms of improving and creating children's wellbeing. Unfortunately the system in Indonesia has not been able to bridge the gap even though the research concept of 'how can schools promote children's wellbeing' is widely offered. This research aims to explore the concept of a well-being school, considering the voices of children, teachers, and parents as the most important aspects in basic education. The participants involved 30 children, 30 parents, and 30 teachers from 3 types of schools (public, private, non-religious, and private Islam) in Yogyakarta Province. Collecting data used Focus Group Discussion and the analysis used Grounded Analysis to create concepts theories. The research showed that schools in Indonesia functioned as the second home after the family. It was found that the term 'fun school' is a model of school which is expected to create happiness and function optimally. The main principles of fun school development are: 1) creating a positive and ethical learning environment, 2) problem-based relevant learning, 3) human and digital interactions, 4) character development through emotional social learning. The foundation of the five principles uses the main values unique to Indonesia, kinship and mutual cooperation. The concept is carried out through the 'Fun School Movement' and is able to create hundreds of model schools in the Yogyakarta, Central Java, Tangerang, Tangsel region, and thousands of school networks in Indonesia with a grassroots approach, has also been adopted by several local governments and is recognized by the Indonesian Ministry of Education and Culture. Banyak penelitian menekankan pentingnya sekolah meluaskan perannya lebih dari sekadar meningkatkan akademik, juga menciptakan well-being anak. Sayangnya sistem di Indonesia belum mampu menjembatani meski konsep penelitian ‘bagaimana sekolah mampu mempromosikan wellbeing anak’ banyak ditawarkan. Penelitian ini bertujuan mengeksplorasi konsep sekolah well-being, yang mempertimbangkan suara anak, guru, dan orangtua sebagai hal terpenting pendidikan dasar. Partisipannya melibatkan 30 anak, 30 orangtua, dan 30 guru dari 3 tipe sekolah (negeri, swasta nonagamis, dan swasta Islam) di Provinsi Yogyakarta. Pengambilan data menggunakan Focus Group Discussion dan analisisnya menggunakan Grounded Analysis untuk menciptakan konsep/teori. Hasil penelitian menemukan, sekolah di Indonesia berfungsi sebagai rumah kedua setelah keluarga. Ditemukan term ‘sekolah menyenangkan’ sebagai model sekolah diharapkan menciptakan kebahagiaan dan berfungsi optimal. Prinsip utama pembangunan sekolah menyenangkan: 1) penciptaan lingkungan belajar positif dan etis, 2) pembelajaran relevan dengan problem based, 3) interaksi manusia dan digital, 4) penumbuhan karakter melalui pembelajaran sosial emosi. Fondasi kelima prinsip menggunakan nilai utama khas Indonesia, kekeluargaan dan gotong-royong. Konsep dijalankan melalui ‘Gerakan Sekolah Menyenangkan’ dan mampu menciptakan ratusan sekolah model di wilayah Yogyakarta, Jawa Tengah, Tangerang, Tangsel, dan ribuan jejaring sekolah di Indonesia dengan pendekatan akar rumput, juga sudah diadopsi beberapa pemerintah daerah dan diketahui Kementrian Pendidikan dan Kebudayaan Indonesia.